Closing gaps in brain disease — from overlapping genetic architecture to common motifs of synapse dysfunction. (February 2018) - Roeper, Jochen
Highlights: Recent progress in the synaptic pathophysiology of brain diseases. Overlapping genetic architecture of brain disorders point to synapse dysfunction. Emerging definition of the activity-dependent synaptic proteome. Disease-relevant interplay between Hebbian and homeostatic plasticity. Common role of macroautophagy and glial-mediated phagocytosis in brain diseases. Abstract : Recent progress in the synaptic pathophysiology of brain diseases is reviewed. To emphasize the emergence of common motifs in synapse dysfunctions across neurodevelopmental, psychiatric and neurological disorders, conventional clinical boundaries are disregarded and a decidedly trans-diagnostic, potentially unifying view of altered synapse function is promoted. Based on the overlapping genetic architecture of brain disorders, which often converges on genes related to synaptic functions, disease-related changes in basic pre-synaptic and post-synaptic communication, neuromodulation-gated changes in Hebbian plasticity, dynamic interactions between Hebbian and homeostatic plasticity, and changes in synaptic maintenance by autophagy and glial-mediated phagocytosis are highlighted.